PENINGKATAN LITERASI TENTANG MENARCHE PADA SANTRIWATI - kustin kustin; kustin; ulfia Fitriani Nafista (LPPM Universitas dr. Soebandi, 2024)
Adolescence is one of the stages in human life. This stage is a crisis stage because it is a transitional stage from childhood to adulthood. According to the characteristics of their sexual development, adolescents generally have developed sexual behavior in the form of heterosexual relationships or dating. One way to minimize the problems of reproductive health problems in adolescents, juvenile delinquency and drug abuse in the community is to directly involve the community itself. These teenagers need increased skills to overcome problems that occur in adolescents, especially reproductive health problems. Menarche is the first menstrual period, a sign of biological readiness, and a sign that the fertile cycle has begun. Readiness to face menarche is a condition that shows that a person is ready with a positive attitude to achieve one of physical maturity, namely the arrival of menarche. various information, but children's ignorance about menstruation can make it difficult for children to accept biological changes in themselves. The purpose of this community service activity is to increase Literacy About Menarche in Santriwati. This activity was carried out in a youth group of 30 teenagers who were students at the Miftahul Ulum Kalisat Jember Islamic Boarding School. The activity was carried out for 1 month to assist the group to increase the literacy of female students related to menarche. The results of forming groups with this empowerment found that there was an increase in literacy among adolescents related to menarche health problems. good menarche initially by 27% increased to 77%. It is hoped that the group that has been formed can continue efforts to increase literacy among peers on the basis of the pesantren culture by optimizing it so that the literacy they have makes teenagers more innovative, creative and also active.